Ectrodactyly its Types and Ways of Treatment - Tukhtanazarova Shavkiya Ibatovna (Genius Journals, 2023)
Ectrodactyly (polydactyly) is a genetic limb developmental disorder in which the hands or feet have an unusual shape and/or extra toes. This developmental disorder occurs during pregnancy when the limbs are still forming
Keywords: ectrodactyly; polydactyly; PPD-improved toe proliferation; HPPD-erctodactyly